Inclusive special education: New theory for the education of children with special educational needs and disabilities (International Seven Journal of Multidisciplinary, 2023)
This article aims to study the inclusion of children with special needs in childhood. Whereas inclusive education and special education are in different philosophies and alternative visions of early childhood education with special education and special needs. They are increasingly considered to be diametrically opposed in their approaches. This article presents a theory of special education that comprises a synthesis. the philosophy, values ​​and practices of inclusive education as interventions, strategies and procedures of special education. The development of inclusive special education aims to provide a framework and guidelines for effective education policies, procedures and strategies for all children as children with special educational needs and disabilities.